2022
DOI: 10.3389/fimmu.2022.832488
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to HLA-Matched Kidney Transplants for African American Patients

Abstract: IntroductionKidney transplants fail more often in Black than in non-Black (White, non-Black Hispanic, and Asian) recipients. We used the estimated physicochemical immunogenicity for polymorphic amino acids of donor/recipient HLAs to select weakly immunogenic kidney transplants for Black vs. White or non-Black patients.MethodsOPTN data for 65,040 donor/recipient pairs over a 20-year period were used to calculate the individual physicochemical immunogenicity by hydrophobic, electrostatic and amino acid mismatch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that HLA matching is harder for Black transplant patients. 27 , 33 Lemieux et al 7 have outlined strategies to improve utility and equity in access to transplantation when incorporating molecular compatibility in organ allocation schemes for nonsensitized and sensitized patients, respectively. In the case of sensitized patients, this strategy aligns with the Eurotransplant Acceptable Mismatch program.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HLA matching is harder for Black transplant patients. 27 , 33 Lemieux et al 7 have outlined strategies to improve utility and equity in access to transplantation when incorporating molecular compatibility in organ allocation schemes for nonsensitized and sensitized patients, respectively. In the case of sensitized patients, this strategy aligns with the Eurotransplant Acceptable Mismatch program.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conclude that the best HLA matches occur when the donor and recipient are of the same race when the transplant comes from a cadaveric donor [37]. In addition, a recent study [38] indicated that HLA-based allocation systems disadvantage Afro-American patients, and this trend has been ongoing for decades [37]. The study reveals that HLA matching is more difficult for Afro-American patients than for white patients, with a lower likelihood that an Afro-American recipient will receive a transplant from a donor with a zero HLA mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, using Organ Procurement and Transplantation Network data for 65 040 donor/ recipient pairs during a 20-y period, it was shown that the retrospective median graft survival in Black recipients was 12.0 y versus 18.6 y in White recipients, 17.2 y for Hispanics and 17.1 y for Asian Americans. 2 AA recipients who were followed for 9 y posttransplant were found to be 1.8 times more likely to experience graft failure compared with White recipients 3 and were more likely to have delayed graft function (odds ratio = 1.63 [95% confidence interval, 1.54-1.73]; P < 0.001), a risk factor for poor allograft survival. 4 Likewise, having an AA kidney donor is associated with worse graft survival (adjusted hazard ratio [HR] = 1.64 [95% confidence interval, 1.24-2.17]).…”
Section: Introductionmentioning
confidence: 99%